Linguistic profiles of children with CI as compared with children with hearing or specific language impairment. Issue 5 (11th February 2016) - de Hoog, Brigitte E.; Langereis, Margreet C.; van Weerdenburg, Marjolijn; Knoors, Harry E. T.; Verhoeven, Ludo
Abstract: Background: The spoken language difficulties of children with moderate or severe to profound hearing loss are mainly related to limited auditory speech perception. However, degraded or filtered auditory input as evidenced in children with cochlear implants (CIs) may result in less efficient or slower language processing as well. To provide insight into the underlying nature of the spoken language difficulties in children with CIs, linguistic profiles of children with CIs are compared with those of hard‐of‐hearing (HoH) children with conventional hearing aids and children with specific language impairment (SLI). Aims: To examine differences in linguistic abilities and profiles of children with CIs as compared with HoH children and children with SLI, and whether the spoken language difficulties of children with CIs mainly lie in limited auditory perception or in language processing problems. Methods & Procedure: Differences in linguistic abilities and differential linguistic profiles of 47 children with CI, 66 HoH children with moderate to severe hearing loss, and 127 children with SLI are compared, divided into two age cohorts. Standardized Dutch tests were administered. Factor analyses and cluster analyses were conducted to find homogeneous linguistic profiles of the children. Outcomes & Results: The children with CIs were outperformed by their HoH peers and peers with SLI on most linguistic abilities. Concerning the linguistic profiles, the largest group of children with CIs and HoH children shared similar profiles. The profiles observed for most of the children with SLI were different from those of their peers with hearing loss in both age cohorts. Conclusions & Implications: Results suggest that the underlying nature of spoken language problems in most children with CIs manifests in limited auditory perception instead of language processing difficulties. However, there appears to be a subgroup of children with CIs whose linguistic profiles resemble those of children with SLI.